THE EFFECT OF WORDWALL MEDIA ON STUDENTS' LEARNING OUTCOMES IN THE SUBJECT OF SCIENCE IN GRADE IV OF SDN 2 MATA IE, KAB. ACEH BESAR - Rahayu, Rani; Mislinawati, Mislinawati; Fitriani, Suci (Universitas Syiah Kuala, 2025)
Low student attention in the learning process can affect less than optimal learning outcomes. One solution that can be applied is the use of interactive learning media, such as Wordwall, which can support learning activities in the classroom and increase student attention to achieve better learning outcomes. This study was conducted with the aim of determining the effect of Wordwall media on student learning outcomes in IPAS subjects in Class IV SDN 2 Mata Ie, Aceh Besar District. This study used a quantitative approach with a Quasi Experimental research type and a Nonequivalent Control Group Design. The population in this study involved all students of class IV SDN 2 Mata Ie totaling 40 students. The sample in the study was divided into two groups, namely the experimental class totaling 23 students and the control class totaling 17 students selected using the total sampling technique. Data collection was carried out by administering a pre-test and post-test using an instrument in the form of a multiple-choice test consisting of 10 questions. To measure significant differences in learning outcomes between the experimental class and the control class, the researcher used the Mann-Whitney test. The results of the data analysis showed the Asymp value. Sig. (2-tailed) of 0.001 0.05, which indicates a significant difference between learning outcomes using Wordwall and conventional learning, so Ha is accepted and Ho is rejected. Based on these results, it can be concluded that there is an influence of Wordwall media on student learning outcomes in IPAS subjects in Class IV SDN 2 Mata Ie Kab. Aceh Besar.